Plant-Growth Promotion and Biocontrol Properties of Three Streptomyces spp. Isolates to Control Bacterial Rice Pathogens - Suárez-Moreno, Zulma Rocío; Vinchira-Villarraga, Diana Marcela; Vergara-Morales, Diana Isabel; Castellanos, Leonardo; Ramos, Freddy A.; Guarnaccia, Corrado; Degrassi, Giuliano; Venturi, Vittorio; Moreno-Sarmiento, Nubia (Frontiers in Microbiology, 2019)
Bacterial Panicle Blight caused by Burkholderia glumae is a major disease of rice, which has dramatically affected rice production around the world in the last years. In this study we describe the assessment of three Streptomyces isolates as biocontrol agents for B. glumae. Additionally, the presence of other plant-growth promoting abilities and their possible beneficial effects upon their inoculation on rice plants was evaluated as an ecological analysis for their future inoculation in rice crops. Two isolates (A20 and 5.1) inhibited growth of virulent B. glumae strains, as well as a wide range of bacterial and fungal species, while a third strain (7.1) showed only antifungal activity. In vitro tests demonstrated the ability of these strains to produce siderophores, Indoleacetic acid (IAA), extracellular enzymes and solubilizing phosphate. Greenhouse experiments with two rice cultivars indicated that Streptomyces A20 is able to colonize rice plants and promote plant growth in both cultivars. Furthermore, an egfp tagged mutant was generated and colonization experiments were performed, indicating that Streptomyces A20 –GFP was strongly associated with root hairs, which may be related to the plant growth promotion observed in the gnotobiotic experiments. In order to characterize the antimicrobial compounds produced by strain A20 bacteria, mass spectrometry analyses were performed. This technique indicated that A20 produced several antimicrobial compounds with sizes below 3 kDa and three of these molecules were identified as Streptotricins D, E and F. These findings indicate the potential of Streptomyces A20 as a biocontrol inoculant to protect rice plants against bacterial diseases.